2014
DOI: 10.1007/s10096-014-2111-1
|View full text |Cite
|
Sign up to set email alerts
|

European Confederation of Medical Mycology (ECMM) epidemiological survey on invasive infections due to Fusarium species in Europe

Abstract: In order to better understand the epidemiology of fusariosis in Europe, a survey collecting information on the clinical characteristics of the patients infected by Fusarium as well as on the infecting isolates was launched. A total of 76 cases of invasive fusariosis occurring from January 2007 to June 2012 were collected and Fusarium isolates were identified by sequencing the translation elongation factor 1α (TEF) gene. Also, antifungal susceptibility was tested by broth microdilution according to the European… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
78
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 27 publications
10
78
0
2
Order By: Relevance
“…The F. andiyazi strain isolated from one patient was the first isolation from a human case that we previously reported [32]. In a recent survey conducted in Europe (involving our region as well), the FFSC was also reported to be prevalent [31]. These data support the view that regional differences exist in the distribution of Fusarium species [10].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The F. andiyazi strain isolated from one patient was the first isolation from a human case that we previously reported [32]. In a recent survey conducted in Europe (involving our region as well), the FFSC was also reported to be prevalent [31]. These data support the view that regional differences exist in the distribution of Fusarium species [10].…”
Section: Discussionsupporting
confidence: 84%
“…Involvement of the skin is another important manifestation of fusariosis and can represent a primary site of infection or a manifestation of secondary metastasis in patients with disseminated fusariosis. Among immunocompromised patients, skin lesions may be the single source of diagnosis [13,31].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro antifungal susceptibility testing showed that discriminating between Fusarium species complexes can indeed be important for appropriate patient treatment, as previously indicated (27). Although amphotericin B was active against all strains analyzed and was the drug of choice for all members of the FSSC and FOSC (i.e., the other antifungals tested had no or only a limited effect), our results suggest alternatives for members of the FFSC and FDSC.…”
Section: Discussionsupporting
confidence: 67%
“…However, according to in vitro testing, antifungal susceptibility profiles have been shown to vary between Fusarium species (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Correct identification to the species or species complex level may thus be crucial for patient treatment, although no in vitro-in vivo correlations have been demonstrated, and treatment is dependent on the type of infection (27). Identification to the species level is also essential for epidemiological purposes.…”
mentioning
confidence: 99%
“…is noteworthy (5,9,26); one study (6) identified only 1/6 F. solani complex when interrogated against the same Bruker library (v1.0). While analyzing Fusarium isolates to the species complex level, rather than to the individual species level may be a limitation, higher species-level discrimination may be unnecessary because susceptibility differences between members of the same species complex do not appear to be clinically relevant (26,33). Species delineation of Fusarium necessitates multilocus gene sequence typing (MLST) incorporating at least four loci, and different MLST schemes are recommended for different species complexes (3,34).…”
mentioning
confidence: 99%